2013
DOI: 10.1177/0022146513497034
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Union Histories and the Mental and Physical Health of Adolescents Born to Unmarried Mothers

Abstract: As nonmarital childbearing becomes a dominant pathway to family formation, understanding its long-term consequences for children’s well-being is increasingly important. Analysis of linked mother-child data from the NLSY79 indicates a negative association of having been born to a never-married mother with adolescent self-assessed health, but not with depressive symptoms. We also consider the role of mothers’ subsequent union histories in shaping the adolescent health outcomes of youth born to unmarried mothers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In these models, the unstable residential group was the reference category and represented the households where biological fathers exited and entered the household only once. As stated previously, much research has indicated a number of positive outcomes for children and adolescents who reside in stable married households (Kelly, 2000), and there is research indicating that children who reside in stable single-parent households are also associated with positive well-being (Demo & Acock, 1996;Williams et al, 2013). Yet, it is unclear whether depressive symptoms vary among children who reside in households where biological fathers exit and enter the household only once from children whose biological fathers exit and enter the household multiple times (i.e., boomerang fathers).…”
Section: Analytic Planmentioning
confidence: 95%
“…In these models, the unstable residential group was the reference category and represented the households where biological fathers exited and entered the household only once. As stated previously, much research has indicated a number of positive outcomes for children and adolescents who reside in stable married households (Kelly, 2000), and there is research indicating that children who reside in stable single-parent households are also associated with positive well-being (Demo & Acock, 1996;Williams et al, 2013). Yet, it is unclear whether depressive symptoms vary among children who reside in households where biological fathers exit and enter the household only once from children whose biological fathers exit and enter the household multiple times (i.e., boomerang fathers).…”
Section: Analytic Planmentioning
confidence: 95%
“…As a result, family structure patterns tend to vary along socioeconomic and racial or ethnic lines, such that unmarried families with children are disproportionately Black and economically disadvantaged relative to their married parent counterparts (Vespa et al, 2013) and are more likely to undergo a family transition (Demo & Fine, 2010;Harknett, 2009). These divergent childbearing and marital trajectories have implications not only for adults' health, economic, and relationship futures (Williams, Sassler, Frech, Addo, & Cooksey, 2011) but also for their children (Williams, Sassler, Frech, Addo, & Cooksey, 2013). On average, the resources married couples are able to invest in their children's healthy growth and development outmatch those of unmarried couples, thus partly driving family structure differences in children's outcomes (McLanahan, 2004).…”
Section: Sociodemographics Family Instability and Child Healthmentioning
confidence: 99%
“…For instance, single mothers in the U.S. seem less happy compared to other adults (Ifcher & Zarghamee, 2014). In addition, children reared by single mothers display increased rates of an assortment of psychological problems such as hyperactivity, problematic peer relations, conduct disorder, and emotional problems (Dunn et al, 1998), poor quality adolescent mental health (Williams, Sassler, Frech, Addo, & Cooksey, 2013), elevated school drop-out rates, and higher probability of teenage pregnancy (McLanahan & Sandefur, 1994). Available evidence further indicates single mothers to be less involved in their children's primary school education (Ressler, Smith, Cavanagh, & Crosnoe, 2017).…”
Section: Adoption As a Difficult Path To Parenthoodmentioning
confidence: 99%